Perspektif Filosofis Sir Muhammad Iqbal tentang Pendidikan Islam - Syarif Hidayatullah (Jurnal Pendidikan Islam, 2013)
These are Sir Muhammad Iqbal’s philosophical views and his thoughts on Islamic education. This is a qualitative descriptive study that describes Iqbal’s philosophical views and his thought on Islamic education. This is a qualitative descriptive study that describes Iqbal’s philosophical views and his thought on Islamic education. The study result is that the philosophical views and his aim of thought on Islamic education are how to create Insan Kamil. Insan Kamil must be a basic goal of the aim of education. According to Iqbal, there are main eight ideas to reconstruct the philosophically Islamic education by improving human dynamics and creativity. They are the concept of individuality, the individual growth, the balance of spiritual and physical, uniting both individuality and society, individual creativity, intelligence and intuition instruction, education of characters, and social education.